2022
DOI: 10.1007/s40123-022-00519-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Transscleral Two-Point Fixation Versus Closed Continuous-Loop Four-Point Fixation of Intraocular Lens in Subluxated Lens Secondary to Marfan Syndrome

Abstract: Introduction To compare the outcome of two different transscleral fixation approaches for posterior chamber intraocular lens (IOL) implantation, a two-point fixation of the Sensar (Allergan) or CZ70BD (Alcon) IOL and a four-point fixation of the Akreos Adapt (Bausch & Lomb) foldable IOL, for treatment of subluxated lenses in Marfan syndrome (MFS). Methods Fifty-three eyes of 33 consecutive patients with subluxated lenses secondary to MFS were studied. Eighteen patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…23 There is only one article published by our institution that compares the outcome of two different transscleral fixation techniques and found that transscleral two-point fixation of IOL has relatively high incidences of pupillary capture of the IOL, and no pupillary capture was seen in all cases of transscleral four-point fixation of the Akreos IOL. 5 More studies that directly compare the effectiveness of transscleral two-point fixation and four-point fixation of posterior IOLs are needed. In our research, no pupillary capture of the IOL occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 There is only one article published by our institution that compares the outcome of two different transscleral fixation techniques and found that transscleral two-point fixation of IOL has relatively high incidences of pupillary capture of the IOL, and no pupillary capture was seen in all cases of transscleral four-point fixation of the Akreos IOL. 5 More studies that directly compare the effectiveness of transscleral two-point fixation and four-point fixation of posterior IOLs are needed. In our research, no pupillary capture of the IOL occurred.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Different techniques of transscleral fixation of PC IOLs have been described, such as two-point fixation and four-point fixation. 5,6 Transscleral two-point fixation of IOL has relatively high incidences of pupillary capture of the IOL. 7,8 For ophthalmologists, the ideal transscleral fixation technique should be simple, quick, minimally invasive, safe, and effective and should offer easy management of potential surgical complications.…”
mentioning
confidence: 99%